Are The Millenials Loyal? - Errie Margery; Wan Suryani (PROCEEDING UMSURABAYA, 2022)
Population Growth according to the results of the Indonesian population census in 2020 Millennials dominate and the characteristics of the Millennial Generation are much different from the previous generation. The Millennial Generation has a disloyal nature, but the Millennial Generation adapts very quickly to technological developments in the era of the industrial revolution 4.0. Millennials get information from the internet to find product or service information, prices and previous user reviews.Keywords: Digital Applications; Millennial Generation; Industrial Revolution 4.0